PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU BATA PADA TOKO SEPATU BATA MTC GIANT PANAM - Fitri, Afma Mega Sari; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research was conducted at the Giant Panam MTC Bata Shoe Shop located on Jl. HR. Soebrantas Km. 12.5 Panam, Pekanbaru. The problem in this study is that for four consecutive years there have been fluctuations that have tended to decrease and have never reached the sales target set by the company. The purpose of this study was to determine the effect of product quality and brand image on the decision to purchase Bata shoes. In this research the method used is descriptive quantitative using the SPSS program. The population in this study were consumers who had bought Bata brand shoes at the MTC Giant Panam shoe store, totaling 18,410 consumers. Samples were taken based on the method with Slovin formula that is 100 respondents and the method of data collection using a questionnaire. Hypothesis testing uses simple linear analysis and multiple linear analysis with the results showing that product quality and brand image have a positive and significant effect on the decision to purchase Bata shoes. With the calculation of the coefficient of determination (R2) simple product quality on the purchase decision obtained R Square value of 0.682 or 68.2% and brand image of the purchase decision obtained a value of 0.532 or 53.2% and the calculation of determination (R2) multiple R Square values obtained amounted to 0.683. This shows that product quality and brand image have an influence of 68.3% on the decision to purchase Bata shoes at the Giant Panam MTC Shoe Shop, while the remaining 31.7% is influenced by other variables not included in this study.Â Keywords: Product Quality, Brand Image, and Purchase DecisionsÂ